Italian approaches to the comparison of religious laws - Cristiana Cianitto (Ancilla Iuris, 2022)
This paper aims at exploring the Italian approach to comparative law of religions by identifying the context, the issues to face in comparing religious laws, and how certain goals have been achieved in Italian legal academia.